When Discounted Rates End: The Costs of Taking Action in the Mortgage Market - Belgibayeva, Adiya; Bono, Teresa; Bracke, Philippe; Clara, Nuno; Cocco, João F; Majer, Tommaso (Review of Financial Studies, 2026)
We combine administrative data with a life cycle structural model that exploits the unique features of the U.K. mortgage market to analyze the sources of inaction and to estimate borrowers’ nonpecuniary remortgaging costs. The utility costs needed to generate a given level of inaction depend on monetary gains from remortgaging and on the importance of those monetary gains for agents, which in turn depend on the (endogenously determined) marginal utility of consumption. The model results reveal significant nonpecuniary costs of action that, when measured as a proportion of borrower income, are larger for the young and for lower-income households.